Multimodal care for the management of musculoskeletal disorders of the elbow, forearm, wrist and hand: a systematic review by the Ontario Protocol for Traffic Injury Management (OPTIMa) Collaboration. Issue 1 (December 2016) - Sutton, Deborah; Gross, Douglas P.; Côté, Pierre; Randhawa, Kristi; Yu, Hainan; Wong, Jessica; Stern, Paula; Varatharajan, Sharanya; Southerst, Danielle; Shearer, Heather; Stupar, Maja; Goldgrub, Rachel; et al.
Abstract Background Musculoskeletal disorders of the elbow, forearm, wrist and hand are associated with pain, functional impairment and decreased productivity in the general population. Combining several interventions in a multimodal program of care is reflective of current clinical practice; however there is limited evidence to support its effectiveness. The purpose of our review was to investigate the effectiveness of multimodal care for the management of musculoskeletal disorders of the elbow, forearm, wrist and hand on self-rated recovery, functional recovery, or clinical outcomes in adults or children. Methods We conducted a systematic review of the literature and best evidence synthesis. We searched MEDLINE, EMBASE, CINAHL, PsycINFO, and the Cochrane Central Register of Controlled Trials from January 1990 to March 2015. Randomized controlled trials, cohort studies, and case–control studies were eligible. Random pairs of independent reviewers screened studies for relevance and critically appraised relevant studies using the Scottish Intercollegiate Guidelines Network criteria. Studies with a low risk of bias were synthesized following best evidence synthesis principles. Results We screened 5989 articles, and critically appraised eleven articles. Of those, seven had a low risk of bias; one addressed carpal tunnel syndrome and six addressed lateral epicondylitis. Our search did not identify any low risk of bias studies examining the effectiveness of multimodal care for the management of other musculoskeletal disorders of the elbow, forearm, wrist or hand. The evidence suggests that multimodal care for the management of lateral epicondylitis may include education, exercise (strengthening, stretching, occupational exercise), manual therapy (manipulation) and soft tissue therapy (massage). The evidence does not support the use of multimodal care for the management of carpal tunnel syndrome. Conclusions The current evidence on the effectiveness of multimodal care for musculoskeletal disorders of the elbow, forearm, wrist and hand is limited. The available evidence suggests that there may be a role for multimodal care in the management of patients with persistent lateral epicondylitis. Future research is needed to examine the effectiveness of multimodal care and guide clinical practice. Systematic review registration number CRD42014009093